Nanomaterials and Biomedicine Therapeutic and Diagnostic Approach - Ray Banerjee, Ena.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book comprehensively reviews the history of nanotechnology, and describes the physiochemical properties of various nanoparticles and their biomedical applications. Covering the biotoxicity of nanoparticles, their bio-distribution and release kinetics, and their role in diagnosis, pre-clinical drug discovery and disease prevention, it also examines the application of nanoscaffolds in tissue engineering and as cell culture templates. Further, the book discusses several fabrication methodologies for regenerative medicine, and explores nanotechnology-based stem cell therapeutics, including stem cell transfection, stem cell delivery, and stem cell expansion for promoting tissue regeneration. Lastly, it addresses the use of DNA barcoding technology from nanosamples for the detection, identification and validation of emerging pathogens, biodiversity and ancient remnants of living specimens, and highlights various strategies for the plant-mediated synthesis of nanoparticles. Given its scope, it is a valuable reference resource for graduate students and researchers interested in understanding the diverse range of biomedical applications of nanoparticles. .
Chapter 1_Introduction to NanoScience, NanoTechnology, and NanoParticles -- Chapter 2_NanoScience and Bioprospecting -- Chapter 3_Nanomaterials and their use in Biomedicine -- Chapter 4_Nano scaffolds and Tissue Engineering -- Module 5_NanoScience Research in Regenerative Medicine -- Chapter 6_Nanomaterials in Food: Probiotics -- Chapter 7_Eco-compatible Single format Nanobioantibody -- Chapter 8_ NanoScience and DNA barcoding.
Keywords: Molecular biology; Nanotechnology; Immunology; Human physiology; Stem cells; Molecular Medicine; Nanotechnology; Immunology; Human Physiology; Stem Cells